Улогата на метакогнитивните стратегии во развивање на вештината читање при изучување на англискиот јазик како странски во високото образование во Косово - Туфекчи, Назли (Филолошки факултет, УКИМ, Скопје, 2018)
Metacognitive strategies are one of widely among teaching strategies that involves planning, self-monitoring and self-evaluation. Metacognition is characterized as a build that alludes to considering one's reasoning or the human capacity to be aware of one's mental procedures. As per Flavell (1976) metacognitive learning is "one's learning concerning one's own particular intellectual procedures and items or anything identified with them, e.g., the learning-applicable properties of data or information". Metacognition is a type of discernment and an abnormal state thinking process that includes dynamic control over subjective procedures. The purpose of the study is to investigate to what extent the University EFL learners employ metacognitive reading strategies in reading comprehension. Further, it aims to research whether University EFL teachers train their students how to be effective readers. Moreover it examines the influence of metacognitive reading strategy training on students’ reading comprehension enhancement. A survey study using MARSI questionnaire was conducted among 473 students. 100 students were chosen from the survey sample and categorized into two groups (experimental = 50; control = 50) for analyzing the role of training on metacognitive strategies in experimental setting. Statistical analysis using MANOVA, ANOVA, correlation and paired sample t-test were performed to assess the research objectives which is discussed in further sections.
Докторска дисертација одбранета во 2018 година на Филолошкиот факултет во Скопје, под менторство на проф. д–р Анжела Николовска.